Does DRD2 polymorphism influence the clinical characteristics of prolactinoma? - Ilhan, MAHMUT MUZAFFER; İLHAN, MAHMUT MUZAFFER; Kahraman, Ozlem Timirci; Turan, Saime; Turgut, SEDA; TURGUT, SEDA; Karaman, Ozcan; KARAMAN, ÖZCAN; Zeybek, Umit; SHUKUROV, Samir; Yaylim, Ilhan; Tasan, ERTUĞRUL; et al. (My University, 2015)
Objectives. - Genetic alterations explaining the clinical variability of prolactinomas still could not be clarified and dopamine D2 receptor (DRD2) polymorphism is a putative candidate for the variable response to dopaminergic treatment. The present study was conducted to investigate the influence of DRD2 TaqI A polymorphism on initial and follow-up characteristics of prolactinoma. Patients and methods. - Seventy-two patients with prolactinoma and 98 age and gender matched control subjects were recruited to the case-control study. Serum prolactin levels were assessed by enzyme-linked immunosorbent assay and DRD2 polymorphism was determined by polymerase chain reaction and restriction length polymorphism analysis. Results. - Decrease of prolactin levels and the tumor shrinkage after cabergoline treatment were 93.9 +/- 5.9% and 58.3 +/- 33.1% in microadenomas and 96.1 +/- 6.1% and 51.7 +/- 29.3 in macroadenomas (P = 0.02 and P > 0.05, respectively). We observed no significant difference for DRD2 genotypes and the alleles between the patients and healthy group (P > 0.05). Prolactin levels before treatment were correlated with tumor diameter before and after treatment and the percentage of prolactin decrease with treatment (P 0.05). Conclusion. - This study revealed that DRD2 TaqI A receptor polymorphism was not associated with the development of prolactinoma and its clinical characteristics. Future studies are needed to clarify the clinical implications of genetic alterations in prolactinoma. (C) 2015 Elsevier Masson SAS. All rights reserved.